European climate pact ambassadors: motivations, strategies, and experiences - Tosun, Jale; Heinz-Fischer, Christin (Bristol University Press, 2026)
European Climate Pact Ambassadors - Motivations, Strategies, and Experiences; Available open access digitally under CC-BY-NC-ND licence. This book focuses on the volunteers who commit to the role of European Climate Pact Ambassador (ECPA) and unpacks who steps up, how they advocate for policy change and what they experience along the way.
Online veröffentlicht: 27. November 2025
Gesehen am 04.12.2025